The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1002/smll.201403155
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes for Dye-Sensitized Solar Cells

Abstract: As one type of emerging photovoltaic cell, dye-sensitized solar cells (DSSCs) are an attractive potential source of renewable energy due to their eco-friendliness, ease of fabrication, and cost effectiveness. However, in DSSCs, the rarity and high cost of some electrode materials (transparent conducting oxide and platinum) and the inefficient performance caused by slow electron transport, poor light-harvesting efficiency, and significant charge recombination are critical issues. Recent research has shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(71 citation statements)
references
References 352 publications
(549 reference statements)
0
68
0
Order By: Relevance
“…Since the conductive nature of carbons is an asset for electron‐transfer processes, there are reports in the literature addressing graphene and graphene oxide,180 carbon nanotubes,181 and CQDs167, 182, 183, 184 as electrodes for dye‐sensitized solar cells185, 186 and perovskite solar cells 187. Moreover, graphene‐based solar cells are also the subjects of photovoltaic studies 188.…”
Section: Foreseen Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the conductive nature of carbons is an asset for electron‐transfer processes, there are reports in the literature addressing graphene and graphene oxide,180 carbon nanotubes,181 and CQDs167, 182, 183, 184 as electrodes for dye‐sensitized solar cells185, 186 and perovskite solar cells 187. Moreover, graphene‐based solar cells are also the subjects of photovoltaic studies 188.…”
Section: Foreseen Applicationsmentioning
confidence: 99%
“…Batmunkh et al have discussed the methods of graphene modifications to improve its interactions with dyes 185, 186, 187. It has been found that chemical treatment of graphene improves its interactions with dyes and has an effect on the size of the bandgap.…”
Section: Foreseen Applicationsmentioning
confidence: 99%
“…A 7:2 mixture of 98% of H 2 SO 4 and phosphoric acid (82%H 3 PO 4 ) (221:8mL) was refrigerated at a temperature of about 4 o C. It was then mixed with about 3.5g of graphite flakes and 13.5g of KMnO 4 (97%). The detail of preparation procedure can be found in [27][28]. The solution'' temperature was controlled by cool 320ml H 2 O together with 4mL hydrogen peroxide.…”
Section: Preparation Of Graphenementioning
confidence: 99%
“…The glass beaker containing 85 mL DI water at 8mg of GO content was "ultrasonicated" for 3hrs after which about 1.7 g of SnCl 2 ·2H 2 O was mixed with 220 mL of 0.12M HCl solution [27][28]. The GO dispersion was mixed with the tin (II) chloride solution and then stirred for 25 minutes.…”
Section: Preparation Of Graphenementioning
confidence: 99%
“…During the last decade or so, the potential benefits of using carbon nanotubes in solar cells has been explored from both a fundamental theory point of view [12], as well as experimentally in a host of different device architectures, including as additives in dye solar cells [34], organic photovoltaics [56], and perovskites [78] and as the active light absorbing component in conjunction with acceptors such as fullerenes [912]. Carbon nanotube–silicon heterojunctions can also function as solar cells [1314] and over the last few years of development the power conversion efficiency (PCE) of these devices has been steadily increasing [1522], with the most recent high efficiency record by Wang et al now standing at ≈17% [23].…”
Section: Introductionmentioning
confidence: 99%